Sphenopalatine neuralgia as a differential diagnosis of complex regional pain syndrome of face - Sanyam K. Mahajan; Vimal Kumar Paliwal (Cephalalgia Reports)
We read with great interest the case report by Dr Hunter Collins, ‘Complex Regional Pain Syndrome Involving the Head and Face After Severe Malignant Otitis Media and Mastoiditis’. This case report is an opportunity to discuss sphenopalatine neuralgia, an entity first described in 1908 by Greenfield Sluder. Due to overlap in the clinical features such as head/face pain, vasomotor/sudomotor features and motor abnormalities associated with pain, and response to sphenopalatine ganglion block, sphenopalatine neuralgia is a close differential diagnosis of complex regional pain syndrome (CRPS) of face. Sphenopalatine neuralgia is associated with many treatable causes related to diseases of paranasal sinuses and nasal septum.